Air-Side Heat Transfer Enhancement Using Vortex Generators on Heat Transfer Surfaces- A Comprehensive Review - Vaibhav Harishchandra Bansode; Munna Verma; Channa Keshava Naik; Amar Pandhare; Chandrashekar Anjinappa; Chander Prakash; Salah Jasim Mohammed; Hasan Shakir Majdi; Ali Majdi (Journal of Heat and Mass Transfer Research)
The main purpose of this article is to provide a critical analysis of published research on these heat transfer surfaces. Important experimental methods and numerical procedures are explained, and many types of vortex generators are described. The phenomenon of flow attributed to vortex generators mounted, connected, pierced, or placed inside surfaces that transmit heat was also examined. In addition, recommendations for applying vortex generator (VGs) technology to improve air-side heat transfer are provided, as well as information on the thermal performance of newly proposed VG heat transfer surfaces. The performance of air-side heating surfaces can often be significantly improved through the use of vortex generators. However, their effectiveness can be greatly affected by many factors, including fluid flow rate, pipe geometry (diameter, shape, pitch, in-line or staggered configuration), fin type, and geometry of the vortex generator (height, length, shape, angle of attack, etc.). Circular fin-tube heat exchangers generally perform worse in terms of thermal-hydraulic efficiency than flat-tube-fin and oval-tube-fin heat-exchanging devices, and more recently, suggested vortex generators. Most current heat exchanger optimization methods focus only on thermal-hydraulic performance.